2023
DOI: 10.1186/s12885-023-10734-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics nomogram for preoperative differentiation of pulmonary mucinous adenocarcinoma from tuberculoma in solitary pulmonary solid nodules

Abstract: Objective To develop and validate predictive models using clinical parameters, radiomic features and a combination of both for preoperative differentiation of pulmonary nodular mucinous adenocarcinoma (PNMA) from pulmonary tuberculoma (PTB). Method A total of 124 and 53 patients with PNMA and PTB, respectively, were retrospectively analyzed from January 2017 to November 2022 in The Fourth Affiliated Hospital of Hebei Medical University (Ligang et a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Several studies have found that radiomics models perform well in classifying malignant from benign solid pulmonary nodules; however, these studies only focused on specific pathological types, i.e. , lung adenocarcinoma and tuberculoma with nodule diameters less than 3 or 4 cm [ 11 , 13 , 15 , 16 ]. Zhang et al [ 16 ] proposed a diagnostic model combining CT and radiomic features and achieved an AUC of 0.85 (95% CI, 0.78–0.91) in the validation cohort, but they focused on solid nodules ranging from 5 to 20 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that radiomics models perform well in classifying malignant from benign solid pulmonary nodules; however, these studies only focused on specific pathological types, i.e. , lung adenocarcinoma and tuberculoma with nodule diameters less than 3 or 4 cm [ 11 , 13 , 15 , 16 ]. Zhang et al [ 16 ] proposed a diagnostic model combining CT and radiomic features and achieved an AUC of 0.85 (95% CI, 0.78–0.91) in the validation cohort, but they focused on solid nodules ranging from 5 to 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics can extract a large number of high-dimensional imaging features and convert this imaging information into quantitative parameters for analysis and modeling [ 14 ], which may serve as a noninvasive method to support personalized clinical decision-making. Previous studies have revealed that radiomics has great potential to support radiologists in identifying benign and malignant solid pulmonary nodules [ 11 , 15 18 ], but few studies have investigated the performance of enhanced CT radiomics in differentiating malignant from benign SSPNs. We aimed to explore the value of enhanced CT-based radiomics in discriminating malignant from benign SSPNs, to develop a combined model based on clinical and radiomics features for the differential diagnosis of SSPNs in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary mucinous adenocarcinoma (PMA) stands out as a distinctive subtype among lung adenocarcinomas, falling within the broad category of non-small cell lung cancer (NSCLC) [ 1 , 2 ]. Characterized by the excessive production of mucin, a viscous, gel-like substance crucial for pathological identification, PMA significantly differs from other lung adenocarcinomas [ 3 , 4 ]. Mucin abundance serves as a diagnostic indicator and influences tumor biology, including invasiveness and metastatic potential.…”
Section: Introductionmentioning
confidence: 99%